Effect of Turbine Blades Transformation on Savonius Turbine Performance - Abdul Alim, Muhammad Iyas; Hadi, Syamsul; Priha Tjahjana, Dominicus Danardono Dwi (Mekanika: Majalah Ilmiah Mekanika, 2022)
This study aimed to determine the effect of the transformation of Savonius turbine blades based on the Coefficient of Performance (Cp)-Tip Speed Ratio (TSR) curve. The transformation referred to here is the change in the blade angle so that the area of the cross-section of the returning blade is changed. Therefore, the opposing torque of the turbine obtained from the airflow is reduced. The specimen has three variations, without transformation or conventional turbine, the transformation of 5°, and transformation of 10°. With the reduction in the cross-sectional area of the returning turbine blade, it is expected that the turbine performance will increase. Experiments were carried out using wind tunnels with load variations at an air speed of 5, 6, and 7 m/s. The experimental result shows that the blade transformation movement causes a shift in the center of mass, increasing the turbine vibration that directly affects turbine performance. The negative effect from the vibration is greater than the positive effect caused by reducing negative torque. The experimental results show that conventional turbines have better performance than turbines with 5° and 10° blade transformations.